Determinants of Simultaneous Election Recapitulation Information System Program in Tomohon City - Pusung, Olivia; Pangkey, Itje; Mokat, Jetty. E (Technium Social Sciences Journal, 2023)
This study aims to analyze the determinants of policy implementation using the Simultaneous Election Recapitulation Information System for Mayors and Deputy Mayors in 2020, using the Milles model qualitative research method which has been modified. The research results show that: a). there is no strong commitment or disposition from the General Election Commission in responding to the unavailability of internet facilities at certain election places and has not seriously trained the technical team implementing the simultaneous election system in implementing the program, b). adequate human resources are not yet available to implement the program, adequate funds are not available, and adequate internet network infrastructure is not yet available, c), the bureaucratic structure is still weak because it does not yet have standard operating procedures specifically strengthened by the Tomohon General Election Commission for implementation simultaneous general elections in 2020. For this reason, it is recommended that a). there is a strong commitment or disposition from the General Election Commission in responding to the unavailability of internet facilities at certain election places and has not seriously trained the technical team implementing the simultaneous election system in implementing the program, b). adequate human resources are available in implementing the program, c). adequate funds are available, d). adequate internet network infrastructure is available, e), bureaucratic structure through the establishment of standard operating procedures specifically by the Tomohon General Election Commission for the implementation of simultaneous general elections in 2020.